La azolla microphylla como suplemento alimenticio en la producción de gallinas criollas (gallus domesticus) en San José de la Parroquia Mercadillo - Arias Villavicencio, Víctor Rosendo (2023)
In poultry farming, the increase of the prices, irregularity in the supply and shortage of feed, constitute new risks that can endanger the operation of this area. In this case, there are local products recognized as non-conventional foods, such is the case of aquatic plants (Azolla sp), which are not usually used in poultry feed, but used in the right way can become an important element in sustainable production systems. Therefore, the objective of this research was to evaluate the effect of Azolla sp microphylla as a feed supplement in the production of Creole hens (Gallus domesticus). For the experimental development of the research, 42 experimental units (Creole hens), aged six months, were needed; two treatments were applied for the study: Treatment 1 (30% Azolla sp + 70% balanced) and Treatment 2 (0% Azolla sp + 100% balanced). The variables studied were feed intake, weight gain, feed conversion, mortality and profitability. The results indicate that feed consumption by the Creole hens is higher in treatment two T2 (0% Azolla sp 100% balanced) with an average of 5880.00 g/day/animal; in relation to the first treatment T1 (30% Azolla sp 70% balanced) 5655.97 g/day/animal. In addition, a weight decrease of -0.18 g/bird/day was obtained in treatment T1; and in treatment T2 a weight increase of 0.07 g/bird/day was obtained. There was no mortality and with respect to profitability there were statistical differences P00.5 between treatments, being 34% for T1 and 26% for T2. In conclusion, Azolla sp sp. is an alternative as a feed supplement in the production of chicken eggs. Key words: poultry, feed, profitability, egg production.